Beyond teaching: understanding the emotional and administrative burden of university academics -A qualitative case study. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background While teaching and research are recognised as the core responsibilities of academic staff, increasing attention is being paid to the hidden demands of university work, specifically emotional labour, administrative duties, and invisible workloads such as student care, departmental service, and institutional compliance. These under-acknowledged responsibilities significantly affect academic productivity, well-being, and institutional engagement. This study investigates how academic staff at a South African university experience and manage these demands, and how they influence teaching, research output, and personal health. Methods A qualitative case study was conducted at a South African public university from January to March 2025. A purposive sample of 20 academic staff (12 women, 8 men) across five faculties, Humanities, Sciences, Engineering, Education, and Health Sciences, was selected. Data collection included 18 semi-structured interviews and 2 focus group discussions, focusing on emotional strain, administrative burden, institutional support, and job satisfaction. Data were analysed using Braun and Clarke’s six-phase thematic analysis, with triangulation enhancing credibility. Results Most participants (85%) reported moderate to severe emotional strain, often linked to student mental health support and unstructured pastoral care roles. Administrative overload, including excessive meetings, compliance reporting, and bureaucratic tasks, was identified as a key barrier to research productivity. Female academics reported disproportionate emotional workload expectations. A perceived lack of institutional support contributed to burnout, with 60% of participants expressing intent to scale back research or exit academia prematurely. Conclusion Emotional and administrative labour are deeply embedded in academic life and significantly affect staff morale, identity, and sustainability. Recognising these demands is crucial to institutional well-being and academic success. Recommendations Universities should formally acknowledge hidden workloads in staff evaluations and planning. Resilience training, digital streamlining, and wellness support systems must be prioritized. Future research should examine long-term effects on staff retention and academic quality.